Limit of detection of troponin discharge strategy versus usual care: randomised controlled trial. Issue 20 (5th May 2020) - Carlton, Edward Watts; Ingram, Jenny; Taylor, Hazel; Glynn, Joel; Kandiyali, Rebecca; Campbell, Sarah; Beasant, Lucy; Aziz, Shahid; Beresford, Peter; Kendall, Jason; Reuben, Adam; Smith, Jason E; et al.
Abstract : Introduction: The clinical effectiveness of a 'rule-out' acute coronary syndrome (ACS) strategy for emergency department patients with chest pain, incorporating a single undetectable high-sensitivity cardiac troponin (hs-cTn) taken at presentation, together with a non-ischaemic ECG, remains unknown. Methods: A randomised controlled trial, across eight hospitals in the UK, aimed to establish the clinical effectiveness of an undetectable hs-cTn and ECG (limit of detection and ECG discharge (LoDED)) discharge strategy. Eligible adult patients presented with chest pain; the treating clinician intended to perform investigations to rule out an ACS; the initial ECG was non-ischaemic; and peak symptoms occurred <6 hours previously. Participants were randomised 1:1 to either the LoDED strategy or the usual rule-out strategy. The primary outcome was discharge from the hospital within 4 hours of arrival, without a major adverse cardiac event (MACE) within 30 days. Results: Between June 2018 and March 2019, 632 patients were randomised; 3 were later withdrawn. Of 629 patients (age 53.8 (SD 16.1) years, 41% women), 7% had a MACE within 30 days. For the LoDED strategy, 141 of 309 (46%) patients were discharged within 4 hours, without MACE within 30 days, and for usual care, 114 of 311 (37%); pooled adjusted OR 1.58 (95% CI 0.84 to 2.98). No patient with an initial undetectable hs-cTn had a MACE within 30 days. Conclusion: The LoDED strategy facilitates safe early discharge in >40% of patients with chest pain. Clinical effectiveness is variable when compared with existing rule-out strategies and influenced by wider system factors. Trial registration number: ISRCTN86184521 .